Divergência genética entre progênies de meios-irmãos de cajueiro anão precoce - Frota Júnior, José Itamar (2012)
The present work was developed in order to characterize and evaluate the genetic diversity of dwarf cashew progenies from Embrapa Agroindústria Tropical using molecular and morphological markers as well as the indication of divergent materials to the breeding program. It was used 50 dwarf cashew progenies from Embrapa Agroindústria Tropical collection located in the Experimental Center of Pacajus, Ceará. In the molecular analysis, each progeny was sampled by collecting leaves from two plants per plot and then analyzed at Embrapa´s molecular biology lab. It was performed DNA´s extractions based on CTAB (Cetyltrimethylammonium bromide) method, adapted by Cavalcanti (2004). ISSR´s markers (Inter Simple Sequence Repeat) were used. Jaccard´s coefficient and UPGMA (Unweighted Pair Group Method with Arithmetic Mean) cluster analysis were applied in the group analysis. Cluster analysis allowed the division into fourteen groups of genetic similarity being the most divergent progenies CNPAT 92-56, 92-62 and 92-385, and the most similar ones CNPAT 92-331 and 92-335. Variables such as plant height, diameter, number of nuts and production, were used in the quantitative analysis. Euclidian distance was used in the genetic distance analysis. UPGMA method were used in cluster analysis. The variable with highest relative contribution to genetic divergence was production, with 97,80%. The UPGMA cluster analysis allowed the division into eleven groups. The most divergent material was CNPAT 92-331 coming from Capisa farm in Piauí state. The most similar materials formed the subgroup I of group I, CNPAT 92-54 and 92-58 with 95% similarity. There is genetic variability, however no direct relationship between molecular and quantitative analysis was found